Aktualisasi Kaidah al-Ḍarūrāt Tubīḥu al-Maḥẓūrāt pada Tindakan Anestesi : Actualization of the Rules of al-Ḍarūrāt Tubīḥu al-Maḥẓūrāt on Anesthesia - Ainun Islamiati; Dewi Indriani; A. Hawariah (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2022)
This study aims to determine the actualization of the rules of al-Ḍarurāt Tubīḥu al-Maḥẓurāt in anesthesia for surgical purposes. This research is a qualitative research, which focuses on the study of manuscripts and texts. By using a normative approach, and juridical. From the results of the study, the actualization of the rules of al-Ḍarūrāt Tubīḥu al-Maḥẓūrāt on anesthesia for surgical purposes is actualized by seeing that anesthesia is forbidden in origin because it can eliminate the mind and substance in anesthetic drugs, so that it is interpreted as khamr. In medical fiqh it is explained that in surgery there are three conditions for the use of anesthesia, one of which is used in emergency conditions, namely when surgery cannot be carried out without anesthesia, then in this condition anesthesia is allowed. This is in accordance with the rules of al-Ḍarūrāt Tubīḥu al-Maḥẓūrāt which explains the permissibility of taking something unlawful in an emergency.